TRANSFORMATIONAL LEADERSHIP IN IMPROVING THE MOTIVATION AND PERFORMANCE OF ORGANIZATIONAL MEMBERS - Hermi Amalia; Eka Andriani; Fadhilah (STMIK Indonesia Banda Aceh, 2026)
Transformational leadership is a leadership style that focuses on the leader's ability to inspire , motivate , and encourage positive change in organizational members . This study aims to examine the effect of transformational leadership on increasing the motivation and performance of organizational members . The method used in this study is a qualitative approach with literature study techniques from various journals , books , and relevant scientific articles . The results of the study indicate that transformational leadership has an important role in creating a productive work environment , increasing member loyalty , and building higher work morale . In addition , transformational leaders are able to provide a clear vision , build good communication , and be a role model for organizational members . Thus , transformational leadership can be an effective strategy in improving the quality of human resources and organizational success .